Oral microbiome and pregnancy: A bidirectional relationship. (June 2021) - Saadaoui, Marwa; Singh, Parul; Al Khodor, Souhaila
Highlights: Pregnancy accompanies a series of changes that increase the susceptibility of the woman to various infections including periodontal disease. Chronic periodontal infections can cause local and systemic inflammatory response. Chronic periodontal infections are associated with adverse pregnancy outcomes. A bidirectional relationship is proposed between the oral microbiota and pregnancy. The combination of personal and professional care for oral health during pregnancy could be crucial to prevent adverse pregnancy outcomes. Abstract: The oral cavity contains the second most complex microbial population within the human body, with more than 700 bacterial organisms. Recent advances in Next Generation Sequencing technology have unraveled the complexities of the oral microbiome and provided valuable insights into its role in health and disease. The human oral microbiome varies dramatically during the different stages of life, including pregnancy. The total viable microbial counts in pregnant women are known to be higher compared to non-pregnant women, especially in the first trimester of pregnancy. A balanced oral microbiome is vital for a healthy pregnancy, as perturbations in the oral microbiome composition can contribute to pregnancy complications. On the other hand, physiological changes and differences in hormonal levels during pregnancy, increase susceptibility to various oral diseases such as gingivitis and periodontitis. A growing body of evidence supports the link between the composition of the oral microbiome and adverse pregnancy outcomes such as preterm birth, preeclampsia, low birth weight among others. This review aims to summarize the dynamics of oral microbiome during pregnancy and to discuss the relationship between a dysbiotic oral microbiome and pregnancy complications.